The LOFAR radio environment - Offringa, A; Bruyn, A; Zaroubi, S; Diepen, G; Martinez-Ruby, O; Labropoulos, P; Brentjens, M; Ciardi, B; Daiboo, S; Harker, G; Jelic, V; Kazemi, S; et al. (2012)
Aims: This paper discusses the spectral occupancy for performing radio astronomy with the Low-Frequency Array (LOFAR), with a focus on imaging observations. Methods: We have analysed the radio-frequency interference (RFI) situation in two 24-h surveys with Dutch LOFAR stations, covering 30-78 MHz with low-band antennas and 115-163 MHz with high-band antennas. This is a subset of the full frequency range of LOFAR. The surveys have been observed with a 0.76 kHz / 1 s resolution. Results: We measured the RFI occupancy in the low and high frequency sets to be 1.8% and 3.2% respectively. These values are found to be representative values for the LOFAR radio environment. Between day and night, there is no significant difference in the radio environment. We find that lowering the current observational time and frequency resolutions of LOFAR results in a slight loss of flagging accuracy. At LOFAR's nominal resolution of 0.76 kHz and 1 s, the false-positives rate is about 0.5%. This rate increases approximately linearly when decreasing the data frequency resolution. Conclusions: Currently, by using an automated RFI detection strategy, the LOFAR radio environment poses no perceivable problems for sensitive observing. It remains to be seen if this is still true for very deep observations that integrate over tens of nights, but the situation looks promising. Reasons for the low impact of RFI are the high spectral and time resolution of LOFAR; accurate detection methods; strong filters and high receiver linearity; and the proximity of the antennas to the ground. We discuss some strategies that can be used once low-level RFI starts to become apparent. It is important that the frequency range of LOFAR remains free of broadband interference, such as DAB stations and windmills.